Assessment of Some Heavy Metals Using Sediments and Bivalvia (Mytilus galloprovincialis) Samples Collected from Tobruk Coast - Fitori, Amani (Scientific Journal for Faculty of Science-Sirte University, 2021)
This study is designed to assess the concentrations of lead, copper, zinc, iron, cadmium and manganese in sediments and bivalvia (Mytilus galloprovincialis) tissues of Tobruk coast. The samples of sediments and bivalvia were collected from four sites around Tobruk city namely as Main port, Ledo, Andolus and Rasbayad (control site), during summer, 2021. The heavy metals of sediments and bivalvia tissues were determined using atomic absorption spectrometry. Also water samples were taken from four sites and physical and chemical properties of water were measured. The results of sediments showed that the Ledo site significantly recorded the higher concentrations of lead (0.624 mg/kg), zinc (73.77 mg/kg), copper (0.450mg/kg) and iron (94.38mg/kg) than those of the other sites, however, the metals of sediments collected from Rasbayad recorded the lowest concentrations. The results of bivalvia tissues revealed that Main port site recorded the greater concentration of lead (0.420 mg/l), zinc (2.185mg/l), cadmium (0.385 mg/l) and copper (3.010 mg/l) than that of other sites. Moreover, Andolus site recorded significantly the higher concentration of iron (14.135 mg/l) than that of other three sites. On the other hand, the Rasbayad recorded the lowest concentration of lead (0.070 mg/l), zinc (0.115 mg/l), cadmium (0.020 mg/l) and copper (0.030 mg/l) in bivalvia tissues. In general, the results indicated a high degree of contamination by heavy metals in sediments and bivalvia of three sites when compared with the control site (Rasbayad) and it is reflect the environmental pressure surrounding the coast of Tobruk, an urgently action is needed to reduce the causes of pollution and contamination by heavy metals.